2016 SIIL Annual Meeting - Women in Agriculture Network (WAgN) Cambodia - Bates, Ricky (Kansas State University, 2016)
Dr. Ricky Bates, PI of the Cambodia subaward funded by the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification (SIIL), presents his project to the SIIL community. Filmed in January 2016.